Reditus Ecologici Plantarum Xerophytarum (Ecological Feedbacks of Xerophytic Plants) - Kholov, Y.; Qahhorov, N.; Soibov, M. (American Journal of Botany and Bioengineering, 2025)
Xerophytic plants, adapted to survive in arid and semi-arid environments, play a pivotal ecological role in maintaining the stability of desert ecosystems. Their physiological, morphological, and biochemical adaptations not only ensure their survival under extreme drought but also generate a series of ecological feedbacks influencing soil fertility, microclimate regulation, and biodiversity conservation. This article analyzes the ecological feedback mechanisms (reditus ecologici) of xerophytic plants from an interdisciplinary perspective, combining plant ecology, soil science, and climate adaptation research. The study highlights the significance of xerophytes in combating desertification, improving water-use efficiency (WUE), and stabilizing fragile ecosystems in Central Asia and other arid regions of the world.